THEORETICAL FOUNDATIONS OF THE DETERMINANTS AND PSYCHOLOGICAL CRITERIA THAT ENSURE FAMILY STABILITY - Shodiyeva, Nodira (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article analyzes the theoretical foundations of the key determinants and psychological criteria that ensure family stability. Factors such as the psychological climate within the family, communication processes, mutual respect, and emotional support are examined as essential components of family stability. The study analyzes theoretical approaches to family relationships and the influence of psychological factors on family stability. The results indicate that psychological balance, social adaptation, and mutual cooperation are of significant importance in ensuring family strength.